Penurunan Logam Fe dan Co Pada Kerang Hijau (Perna viridis) dengan Metode Perendaman Larutan Belimbing Wuluh: Reduction Fe and Co Metals in Green Mussels (Perna viridis) by Soaking in Starfruit Solution - Widiyanto, Holisha; Asad, Hafidz Al; Sriwijayanti; Susvira, Dian; Situmeang, Boima (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Green mussels with the Latin name Perna viridis are an animal that lives in the ocean and is a type of shellfish that is widely consumed by the public. Along with time, the emergence of factories that can pollute the oceans can cause contamination of marine life in it, one of the pollutants is the heavy metals of Fe and Co. The accumulation of heavy metals Fe and Co in green mussels can be toxic to people who consume them. This study aims to determine the concentration of heavy metals Fe and Co in green mussels before and after immersion in starfruit solution. Tests for immersion of the starfruit solution were carried out at 15, 30, and 45 minutes, then the destruction results were analyzed using inductively coupled plasma (ICP) with the calibration curve method. The Fe content in the green mussel sample before treatment was 2.946 mg/kg and the Co content in the green mussel sample before treatment was 2.6081 mg/kg. After soaking in starfruit solution for 15, 30, and 45 minutes, the Fe metal was 1.572 mg/kg, 1.275 mg/kg, and 1.035 mg/kg and the Co metal was 1.572 mg/kg, 1.275 mg/kg, and 0.683mg/kg. Research of immersing starfruit solution with soaking for 15, 30, and 45 minutes is effective in reducing levels of heavy metals Fe and Co in green mussels. The highest reduction was observed during a 45-minute immersion, with a decrease of 64.87% for Fe and 73.81% for Co, respectively.